German medical students' views regarding Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS): a cross-sectional survey - Li Schimmerl; Bernhard Haller; Alena Buyx; Stuart McLennan (Springer, 2024)
Abstract Background Myalgic encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a challenging disease pattern and has gained increasing scientific and public interest in recent years due to the Corona pandemic and Long-Covid. The aim of this study was to investigate (1) medical students' health-related control beliefs, (2) students' awareness and views about ME/CFS at the beginning of their medical education, and (3) to examine whether there are correlations between students' health-related control beliefs and their views about ME/CFS. Methods A cross-sectional online-survey was conducted in October 2020 with all new medical students at the Ludwig Maximilian University of Munich and the Technical University Munich. Results A total of 251 students completed the survey, representing a response rate of 27.0% (251/929). The examined health related locus of control of the students was predominantly internal oriented. Students' awareness about ME/CFS at the beginning of their medical education were found to be low: 46,8% (117/250) of the students surveyed disagreed that they have heard or read about ME/CFS and 81,6% (204/250) disagreed that they feel sufficiently well informed about the disease. A possible correlation between students' health-related locus of control and their views regarding ME/CFS-specific issues was found: The higher the students' internal locus of control, the less they favored a strict separation of mental and physical suffering in medical practice, the less they believed that psychological causes for an illness should only be sought when no physically objective causes could be found, and the less they agreed that there is no indication for therapy if a disease is not objectively detectable. Conclusions As ME/CFS is a medical challenge and increasingly relevant in medical practice, the fact that 50% of medical students have never heard of this disease underscores the need for awareness and education. We found that the majority students in the sample largely have an internal health related locus of control. They rate their own influence on their health higher than those with an externally oriented control conviction.